Pedo-geotechnical evaluation of subgrade soils along failed Ago-Iwoye/Ilisan road, part of southwestern Nigeria (2024)
This study utilized the principles of soil mechanics and the physiograph concept to establish pedo-geotechnical patterns of natural soils for the design of pavement structure. A total of 60 disturbed and undisturbed subgrades were sampled from 10 locations at the SB segment, 10 locations through the TZ and 10 locations at the BC end. A series of specific gravity, grain-size distribution, consistency limits, compaction characteristics (unsoaked and soaked CBR) and shear strength parameters were performed. Field observation and test results revealed that the studied area consists of extensive sand, interposed with clayey sand bodies along the SB segment. Also, particles of various sizes at the TZ and heterogeneous sandy clay in the BC segment were noted. Soils from the TZ under soaked conditions have the highest CBR (80.0–88.1%), MDD (19.0–19.1 kN/m3) and the lowest OMC (10.2–10.5%) values. They also have the highest cohesive strength (72.0–80.0 kN/m2) and angle of internal friction (14°−16°). Comparison among properties revealed that soils from the SB area especially, the TZ have much higher subgrade ratings compared to the soils from the BC terrain. The result revealed that the physiography factors affect the performance of the entire pavement structure.